2013
DOI: 10.1093/trstmh/trt057
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B in two period birth cohorts of Bolivian children: effect of universal vaccination

Abstract: This study identified a persistent low seroprevalence of hepatitis B infection in spite of a decade of universal immunization, and low long-term humoral immunity against HBV infection in vaccinated children in Cochabamba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In an study in Egypt It has also been reported that children with diabetics may not have effective concentrations of anti-HBs antibody after the primary vaccination (27). Moreover, there is a report of low long-term humoral immunity against HBV infection in vaccinated people in Bolivia (28). Patients with HIV infection may also lose their HBV vaccination response rapidly after completing the vaccination, so they need to be evaluated 6-12 months after finishing the primary vaccination series (29).…”
Section: The Present Situation Several Years After Starting the Sumentioning
confidence: 99%
“…In an study in Egypt It has also been reported that children with diabetics may not have effective concentrations of anti-HBs antibody after the primary vaccination (27). Moreover, there is a report of low long-term humoral immunity against HBV infection in vaccinated people in Bolivia (28). Patients with HIV infection may also lose their HBV vaccination response rapidly after completing the vaccination, so they need to be evaluated 6-12 months after finishing the primary vaccination series (29).…”
Section: The Present Situation Several Years After Starting the Sumentioning
confidence: 99%
“…In Bolivia, another country with low endemicity prior to introduction of universal vaccination among children aged <1 year, a serological study with limited sample size (424 individuals) identified a persistent low prevalence of HBV infection after a decade of universal vaccination among children ages 5–16 years [35]. Quebec and British Columbia, like other provinces of Canada, initially opted for school-based pre-adolescent or adolescent HB immunization programs instead of routine infant vaccination.…”
Section: Resultsmentioning
confidence: 99%